2016
DOI: 10.1371/journal.pone.0166305
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Levels of Pre-Treatment HIV-1 Antiretroviral Drug Resistance Detected in the First South African National Survey

Abstract: BackgroundIn order to assess the level of transmitted and/or pre-treatment antiretroviral drug resistance to HIV-1, the World Health Organization (WHO) recommends that regular surveys are conducted. This study’s objective was to assess the frequency of HIV-1 antiretroviral drug resistance in patients initiating antiretroviral treatment (ART) in the public sector throughout South Africa.MethodsA prospective cross-sectional survey was conducted using probability proportional to size sampling. This method ensured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 28 publications
7
32
1
Order By: Relevance
“…Ten percent of the recently acquired HIV infections in donors had sequences consistent with transmitted drug resistance, similar to the finding of 9% ART drug‐resistant HIV in the first South African national survey of pretreatment resistance . There were too few non–subtype C cases to investigate any differences in drug resistance prevalence between subtypes.…”
Section: Discussionsupporting
confidence: 64%
“…Ten percent of the recently acquired HIV infections in donors had sequences consistent with transmitted drug resistance, similar to the finding of 9% ART drug‐resistant HIV in the first South African national survey of pretreatment resistance . There were too few non–subtype C cases to investigate any differences in drug resistance prevalence between subtypes.…”
Section: Discussionsupporting
confidence: 64%
“…One population-based study in South Africa found evidence of DRM in 7% of ART-naïve patients in rural KwaZulu-Natal in 2012, similar to our findings of DRMs in 8% of our 2014 North West population sequenced pre-treatment. Clinical cohort studies in sub-Saharan Africa have found a similar prevalence of drug resistance mutations in 6-11% of ART-naïve patients [11,20,22]. If our study participants reported ART initiation accurately, 8% would represent the baseline estimate of transmitted resistance in the population, most of which was NNRTI only (63.0%), with fewer mutations representing PI/ NRTI resistance (25.5%) and even fewer being single PI resistance (11.5%).…”
Section: Discussionmentioning
confidence: 99%
“…For these patients, DRM could lead to first-line failure. Recent studies have demonstrated that the prevalence of transmitted and acquired drug resistance is increasing in RSA [20]. The cost in a program as large as South Africa's makes baseline DRM testing prior to ART initiation to inform regimen selection largely infeasible; however NHLS has instituted alert reports for adherence counseling and DRM testing should be made available when treatment failure is evident.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach of understanding the microbial resistance levels in the general population is not new: for example, it is being applied in HIV drug resistance surveillance. [10] In view of the enormous challenge posed by the surge in antibiotic resistance in SA and globally, new strategies are needed to improve our understanding of the antibiotic resistance landscape.…”
Section: Guest Editorialmentioning
confidence: 99%